The relationship among hopelessness, suicide risk, body mass index and eating motivations in major depressive disorder comorbid with obesity: a case–control study - Fatma Gül Helvacı Çelik; Meltem Hazel Şimşek; Meltem Puşuroğlu; Ulaş Korkmaz (Annals of General Psychiatry)
Abstract Objective Major Depressive Disorder (MDD) is a significant mental health problem, frequently comorbid with both physical and psychiatric disorders. The association between MDD and obesity is not fully understood. Eating motivations (EMs), which relate to why and how individuals choose to eat, may be associated with disorders like obesity and MDD. Hopelessness and suicidal ideation are common symptoms of MDD. This study aimed to evaluate the relationship between EMs, depression, body mass index (BMI), hopelessness, and suicidal ideation in normal-weight and obese MDD groups compared to healthy controls. Method The study included 50 patients with MDD and normal weight (BMI 18.5–24.9), 50 patients with MDD and obesity (BMI > 30), and 50 healthy control participants (BMI 18.5–24.9). The majority of participants were women (74% in obese MDD, 70% in normal-weight MDD, 56% in the control group). The age of the groups was similar for the normal-weight MDD and control groups, but the obese MDD group was older (control: 32.72 ± 10.07, normal-weight MDD 33.42 ± 10.24, obese MDD 39.52 ± 10.67, p = 0.002). Regarding BMI, it was as follows: control: 21.61 ± 1.92, normal-weight MDD 23.54 ± 3.60, and obese MDD 35.30 ± 5.07. Sociodemographic data form, Beck Depression Inventory, Beck Hopelessness Inventory, Suicide Ideation Scale and Eating Motivation Questionnaire were administered. Results No significant differences were found between the MDD groups in terms of Beck Depression Inventory (BDI), Beck Hopelessness Inventory (BHI), and Suicidal Ideation Scale (SIS) scores. Significant differences were observed among all groups in most subtypes of EMs. In the obese MDD group, habits, traditional eating, price, visual appeal, and affect regulation were correlated with suicide attempts. Only traditional eating remained associated with suicide attempts, where a one-unit increase in the traditional eating score explained a 0.724-unit increase in suicide attempts. Additionally, emotion regulation was a significant predictor of suicidal ideation in the obese MDD group, where a one-unit increase in emotion regulation explained a 0.885-unit increase in suicidal ideation. Conclusions The differentiation between suicidal ideation and EMs in obese and normal-weight MDD groups is crucial. The observed differences in EMs among the three groups with similar sociocultural characteristics are noteworthy. Clinicians should assess eating motivations as part of suicide risk evaluations in patients with comorbid MDD and obesity. Longitudinal studies are needed to clarify causal relationships between these variables.